Machine learning assisted remote forestry health assessment: a comprehensive state of the art review - Estrada, Juan Sebastián; Fuentes, Andrés; Reszka, Pedro; Auat Cheein, Fernando (Frontiers in Plant Science, 2023)
Forests are suffering water stress due to climate change; in some parts of the globe, forests are being exposed to the highest temperatures historically recorded. Machine learning techniques combined with robotic platforms and artificial vision systems have been used to provide remote monitoring of the health of the forest, including moisture content, chlorophyll and nitrogen estimation, forest canopy, and forest degradation, among others. However, artificial intelligence techniques evolve fast associated with the computational resources; data acquisition, and processing change accordingly. This article is aimed at gathering the latest developments in remote monitoring of the health of the forests, with special emphasis on the most important vegetation parameters (structural and morphological), using machine learning techniques. The analysis presented here, gathered 108 articles from the last 5 years, and we conclude by showing the newest developments in AI tools that might be used in the near future.